Meldonium – A High Potential Drug. Literature Review - Ochwat, Michał; Dąbek, Katarzyna; Sudoł, Maria; Piekarska, Martyna; Skowronek, Anna; Mierzwa, Gabriela; Kajtel, Aleksandra; Ochwat, Maria (Quality in Sport, 2024)
Introduction and purpose: Meldonium is a long-established substance. Initially, the substance was only available in the former Soviet Union; now the drug can be obtained, for example, in Poland. Originally, its action was observed in the cardiovascular system as an antianginal drug. Today meldonium is already being used in ischaemic heart disease and chronic heart failure. This review provides exhaustive account of the pharmacological properties and clinical applications of the drug meldonium, with a particular emphasis on its biochemical effects, pharmacokinetics, and potential for performance enhancement in athletes. Material and methods: The literature available in PubMed and Google Scholar databases was conducted using the keywords. Description of the state of knowledge: Meldonium acts as a γ-butyrobetaine hydroxylase inhibitor, preventing de novo synthesis of carnitine and its absorption at the intestinal level. This leads to inhibition of ß-oxidation and activation of glycolysis, which is recognised as an anti-ischaemic and cardioprotective mechanism. The results of studies indicate the potential of this drug for the treatment of neurological and ischemic conditions. Meldonium is likely to improve performance in sport, which led to the compound's inclusion on the World Anti-Doping Association's list of banned substances. Conclusions: Despite the high potential shown in studies to date, new, more thorough studies are needed to confirm the effectiveness of meldonium.